Biological Synthesis of Copper Nanoparticles using Tinospora cardifolia Extract and their Antioxidant Activity - Sulekha; Dr. Jitendra Kumar Gupta; Anil Singh (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In the current study investigates the antioxidant properties of Tinospora Cardifolia extract and the biological production of copper nanoparticles. Tinospora cordifolia is used in this work to produce copper nanoparticles, which are then characterized by FTIR, XRD, and TEM analysis. The plant extract was prepared from the leaves of Tinospora cordifolia. The test procedures for antibacterial, phytochemical, and antioxidant properties are also explained. The results were collected and statistically analyzed. Tinospora cordifolia extract was used as a reducing agent in the synthesis of CuNPs using the chemical reduction procedure because of its high phenolic and flavonoid content as well as its antibacterial and anti-inflammatory qualities. The goal of this effort was to find a more ecologically friendly way to produce copper nanoparticles in order to give pharmacological evidence against the antioxidant activity. Further study and in vivo studies are necessary to further understand the potential phenolic and flavonoid compounds found in Tinospora cordifolia’s leaves, bark, and roots.